(untitled) (Advancements in Homeopathic Research, 2025)
The skin is one of the largest and most important organs in the body and comprises approximately 16% of the human body weight. It has a number of physiological functions that are essential to maintaining homeostasis, protection and social interaction. Protection, thermoregulation, sensation, water storage, absorption, expression, synthesis of vitamin D. The skin is the main interface between the individual and the environment. It therefore has essential physiological functions which allow the individual to live safely, even under changing external conditions which might pose potential threats. The skin has 3 layers—the epidermis, dermis, and hypodermis, which have different anatomical structures and functions. The epidermis is derived from ectodermal tissue. The dermis and hypodermis are derived from mesodermal tissue. Nerves of the skin include both somatic and autonomic nerves. The somatic sensory system transmits pain (nociception), temperature, light touch, discriminative touch, vibration, pressure, and proprioception sensations to the central nervous system. Autonomic innervation controls vasculature tone, hair root pilomotor stimulation, and sweating. The free nerve endings extend into the epidermis and are responsible for sensing pain, heat, and cold.